P2 Manifests Subjective Evaluation of Reward Processing Under Social Comparison - Zou, Feng; Li, Xiaoya; Chen, Fenfang; Wang, Yao; Wang, Li; Wang, Yufeng; Wu, Xin; Zhang, Meng (Frontiers in Psychology, 2022)
Several recent studies have found that when the other's gain is greater, even a reward may seem like a loss and lead to a negative experience. These studies indicate the complexity of reward evaluation in the context of social comparison. The satisfaction rating of reward outcome appears to not only depends on objective social comparison but also on subjective evaluation. However, little is known about the neural time course of subjective evaluation. Therefore, we employed a 2 (subjective evaluation: advantageous vs. disadvantageous) by 2 (comparison directions: upward vs. downward) within-subjects factorial design, in which we manipulated the reward distribution for the subjects. Electroencephalography responses were recorded while two subjects concurrently but independently performed a simple dot-estimation task that entailed monetary rewards. Behavioral results showed that the subjects were more satisfied with the advantageous distribution, regardless of upward or downward comparison. Analysis of Event-related potentials (ERPs) revealed that disadvantageous distribution elicited a larger P2 than advantageous distribution, and this effect was not modulated by comparison direction. In contrast, the late positive potential (LPP) showed an effect of comparison direction independent of subjective evaluation. The data suggest that subjective evaluation act upon the early stage of reward processing and manifest in the P2 component, whereas social comparison plays a role in the later appraisal process.